2014
DOI: 10.1002/lary.24754
|View full text |Cite
|
Sign up to set email alerts
|

Emergencies in otolaryngology–head and neck surgery bootcamp: A novel canadian experience

Abstract: This first Canadian OTO-HNS bootcamp demonstrated the feasibility and effectiveness of conducting a centralized bootcamp for regional training centers spanning multiple states/provinces and languages. Future bootcamps will be held annually and will ideally continue the natural evolution of surgical, hands-on training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 10 publications
5
55
0
Order By: Relevance
“…Although statistically less well thought of, scores for the control setting were also good, confirming that the control teaching was of high quality and a good comparator (as should be expected when the majority of the slides that were presented to each group were the same). The results from the modified DREEM questionnaire and recommendation question are in line with other studies that have shown that simulation is popular with trainees, boosts confidence, and is perceived as an effective method of training …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although statistically less well thought of, scores for the control setting were also good, confirming that the control teaching was of high quality and a good comparator (as should be expected when the majority of the slides that were presented to each group were the same). The results from the modified DREEM questionnaire and recommendation question are in line with other studies that have shown that simulation is popular with trainees, boosts confidence, and is perceived as an effective method of training …”
Section: Discussionsupporting
confidence: 88%
“…Other groups have used epistaxis mannequins, with fake blood and active bleeding, and porcine larynx is often used to facilitate surgical airway practice . Cadavers have traditionally been used to practice temporal bone dissection or sinus surgery, but have also been used in emergency simulation such as epistaxis or post‐tonsillectomy bleeding . Technologically advanced mannequins are also available that can be programmed to simulate presentations such as stridor, pharyngeal edema, or trismus, with realistic functions such as tachycardia and altered ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…The components of the WSC were highly rated and deemed valuable by the students. The self-assessed perceived gains in practical surgical skills were significantly increased because of the course, and are keeping with other published training reports 6 7…”
Section: Discussionsupporting
confidence: 89%
“…The most basic of these are reports that merely describe the design and structure of such a course 16. Next are studies of face and content validity in which participants rate the course content,6 followed by studies (such as this one) where a self-assessment of readiness by participants is evaluated 19. While useful in providing feedback to guide curricular development, reports such as these do not measure any real gain in knowledge or skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation